Conflict in the Western Sahara from the point of view of international humantarian law - Bagatsky, E. V.; Багатский, Е. В. (My University, 2012)
This article is dedicated to the evaluation of the confl ict in the West Sahara from the point of view of international humanitarian law, and in particular to the observance of the standards of this division of international law in the course of this confl ict. In the framework of the study there were used international documents, containing the basic conditions of international humanitarian law. Analyzing the course of events, and referring to the above-mentioned documents and to the exist175 ing works of domestic and foreign researchers, the author gives the legal estimation of the confl ict in the West Sahara for each of the stages of its active phase, which lasted from 1973 until 1991.
Bagatsky E. V. Conflict in the Western Sahara from the point of view of international humantarian law / E. V. Bagatsky // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип. 46. – С.174-178.
Keywords: конфликт в Западной Сахаре; международное право; международные документы; международное гуманитарное право; конфлікт в Західній Сахарі; міжнародне право; міжнародні документи; міжнародне гуманітарне право; the conflict in Western Sahara; international law; international documents; international humanitarian law